Intersectoral Mobility and Short-Run Labor Market Adjustments - Chan, William (Journal of Labor Economics, 1996)
This article presents a model of labor market adjustments as a sequential process of reallocation among various market and nonmarket sectors. Training costs introduce friction into the process, while fixed costs of working limit work sharing, resulting in unemployment. Adjustments in sectoral labor market variables to demand shocks can follow very different patterns, depending on relative demands and the expected duration of the shocks. In particular, a permanent boom in a sector may result in an initial increase in unemployment and reduction in working hours even as employment increases, reflecting contemporaneous substitution between the margins and intertemporal substitution in recruitment.